On the suitability of dynamic languages for hot‐reprogramming a robotics framework: a Python case study. (15th October 2012) - Ortin, Francisco; Mendez, Sheila; García‐Díaz, Vicente; Garcia, Miguel
SUMMARY The development of service robots has gained more attention over the last years. Advanced robots have to cope with many different situations emerging at runtime, while executing complex tasks. They should be programmed as dynamically adaptive systems, capable of adapting themselves to the execution environment, including the computing, user, and physical environment. Recently, dynamic languages are becoming widely used because of the high runtime adaptability they offer. Therefore, we have analyzed the suitability of these languages to implement robotic systems with high runtime adaptability requirements, using Python as case study because of its maturity. To evaluate their suitability, we have implemented a reflective robotics framework that can be programmed in both Java and any dynamic language supported by the standard Java Scripting API. An example scenario has been developed using Python to show how its distinguishing meta‐programming features have facilitated the development of runtime‐adaptable robotics services. Copyright © 2012 John Wiley & Sons, Ltd.